Peran Pendidikan Berbasis Pesantren dalam Mewujudkan Indonesia Madani di Era Globalisasi - Asbarin Asbarin; Kumillaela Kumillaela; Dita Armitha Sari (Tarbiyatuna: Jurnal Pendidikan Ilmiah, 2018)
Education is one of the factors that determine the progress of the nation in the future. Education also has an important role in establishing the potential possessed by every individual so that it can develop optimal and beneficial to the progress of the nation. Innovation in development education includes a wide range of dimensions, which are dimensions of social, cultural, economic and political. In social perspective, education can generate the educated people who have an important role in the community environment changes. In cultural perspective, education is the most effective means in the realization of religious values in the social environment of a nation. While in political perspective, education also has a very important role in developing the capacity of the individual to be obedient citizen. In this globalization era, the competitiveness among Nations in the field of education is more increasing. It can be seen from the progress of the nation in generating younger generation who can compute the current globalization. The optimal result can achieve, if we can supervise institutions that not only understand the General Sciences, but also the religious sciences. Without religious studies, graduates can have limitations, when faced with the current globalization in the present and future. The results of this paper, mention the existence of the role, contribution and the implications of a boarding school in an attempt to print the generation of tough, able to become a professional ulama, and character ulul albab, so being able to control the Indonesian people to face the current Globalization.